Profit-Shifting Activities in the Mining Sector: Evidence from the Czech Republic - Daniel Anarfi (European Journal of Business Science and Technology, 2017)
The aim of this paper is to measure the magnitude of profit shifting in the Czech Mining industry. The paper source data from AMADEUS provided by the Bureau van Dijk for the 10-year period 2005-2014 to seek evidence of profit-shifting activities and measure the magnitude. The paper applies panel regression model in the analysis to seek evidence and measure the magnitude of profit shifting using random effect model estimations. The paper therefore analyses tax effects on capital structure of subsidiary firms as a means of profit shifting and the results was that, there is substantial evidence of profit shifting with different magnitudes in separate model specifications.